Current Status of Orbital Implants in Pakistan - Sahaf, Imran Akram (Pakistan Journal of Ophthalmology, 2008)
Anophthalmic socket reconstruction should start at the time of primary surgery. An orbital implant is regarded as the first step for making platform for an ocular prosthesis. Not long ago quite a few ophthalmologists in Pakistan believed that no implantation should be done at the end of evisceration for endophthalmitis thinking that infection may persist. However, now mostly an appropriate sized acrylic ball is implanted after evisceration and a conformer is inserted. Evisceration and acrylic ball implantation is also used by some surgeons in the cases of painful blind eye. Similarly after enucleation for ocular malignancy no implantation was done with a false belief that recurrence of tumour may be masked. On the contrary it is now believed that an implant makes detection of recurrence much easier. However, previously available implants had several problems. Allen implant has truncated front surface with sharp edges. Hence, it not only gives poor volume replacement but there is also an increased risk of wound dehiscence and implant exposure.